Two organophosphorus pesticides: methyl parathion and dicapthon. Issue 10 (28th September 2014) - Baughman, Russell G.; Hall, Gabriel B.
<x xml:space="preserve">Abstract</x> Structural studies performed in this laboratory of organophosphorus pesticides continue with these related compounds. The –NO2 groups of methyl parathion (systematic name: dimethyl 4‐nitrophenyl phosphorothioate, C8H10NO5PS) and dicapthon (systematic name: 2‐chloro‐4‐nitrophenyl dimethyl phosphorothioate, C8H9ClNO5PS) make dihedral angles of 10.67 (8) and 5.8 (1)°, respectively, with the planes of their attached rings, which accompanies angular distortion at the ring C atoms to which the –NO2 groups are attached. Similar distortions are observed at the C atom to which the thiophosphate groups are attached. Significant differences in distances and angles around the phenolic O, versus the –OMe groups, explain why it is the site of hydrolysis for these compounds. A comparison of a torsion angle involving the thiophosphate group and phenolic O atom with similar pesticide structures is given and indicates steric influences on that angle.